Recreational Therapists' Practice, Knowledge, and Perceptions Associated with Animal-Assisted Therapy. - Barbosa Dunlap, Kimberly; Miller, Kimberly D.; Kinney, Judy S. (Therapeutic Recreation Journal)
Animal-assisted interventions have been implemented by health care professionals because of the therapeutic value of animal interactions. The purpose of this study was to survey Certified Therapeutic Recreation Specialists (CTRSs) to (a) determine the prevalence of Animal Assisted Interventions (AAI) implemented by recreational therapists, and (b) understand the knowledge and barriers to AAT implementation that exist for recreational therapists. A total of 123 Certified Therapeutic Recreation Specialists participated in the study (a 6.2% response rate). A significant difference was found in the AAT goal of improving social interaction by population. Those working in physical medicine and rehabilitation reported less improvement than those in behavioral health, geriatrics and community agencies. CTRSs indicated there is a need for additional education and trainings on AAT practice. Many CTRSs surveyed identified the lack of registered animal/handler teams in the area as a major barrier to implement AAT.